89B Section B: Hair Transplantation in South Asian Hair (Hair Transplantation, 2023)
Hair restoration in South Asian patients has certain specific features because of ethnic characteristics, cultural aspects, and attitudes. Recent economic liberalization, Internet, and globalization have led to changes in attitude and increase in hair transplantation.
Keywords: South Asian hair; ethnic features